Penjatuhan Talak Terhadap Istri dengan Alasan Tidak Mendapatkan Keturunan - Nurfitria, Ida; Susanti, Dyah Ochtorina; Widiyanti, Ikarini Dwi (Lentera Hukum, 2015)
The imposition of divorce is included in one of the marriage break-ups due to divorce, the divorce should only be made based on divorced reasons contained in the rule of positive law. In this study, the panel of judges gave the stipulation in accordance with the provisions of Law number 1 of 1974 on marriage and the Compilation of Islamic Law. This type of research uses the juridical normative (legal research) that examines legal issues associated with positive law rules, principles, and norms. The conclusion of this study indicates that the imposition of divorce against the wife with the alibi that the wife can not give ancestry can not be an excuse to do divorce. Because of this divorce is granted, based on the judge's reasons for the imposition of divorce due to continuous disputes and quarrels in accordance with the provisions in the Compilation of Islamic Law. Due to the imposition of divorce caused the breaking of marriage among the parties. KEYWORDS: Divorced, The Imposition, Verdict, Law Effect